Application of in vacuo chemical modification for protein characterization and enhancement of the physico-chemical properties of proteins - Pham, Van Thong (University of Ottawa (Canada), 2008)
Chemical modification of proteins is a major experimental tool for the study of structure-function relationships in proteins and in pharmaceutical and industrial applications of proteins. Many chemical modifying reagents and strategies have been developed for a wide variety of applications. The vast majority of these procedures are designed to be carried out in aqueous solution which limits the range of chemical modifying reagents as well as the types of modifications that can be carried out. In vacuo chemical modification is a methodology in which proteins are chemically modified in the lyophilized state and modifications can be made which are difficult or impossible to carry out in aqueous solution. Three different in vacuo chemical modifications, which cannot be carried out in aqueous solution, are used to develop novel applications for structural studies on proteins, for improvement of the physical properties of proteins, and for practical applications. The first is the in vacuo methylation of carboxyl and amino groups of proteins with iodomethane. Novel diagonal electrophoretic procedures, which can be used in structural studies or proteomic applications, were developed for the selective isolation of peptides derived from either the carboxyl terminus or the amino terminus of proteins. The second is the in vacuo glycation of proteins in which a reducing sugar is covalently attached to the amino groups of a protein without the use of chemical activating reagents. Glycated trypsin, or glycotrypsin, was shown to undergo greatly reduced autolysis thereby increasing its stability and reducing contaminating autolytic products in tryptic digests of proteins. In vacuo glycation was also shown to improve the thermostability of trypsin and chymotrypsin, and evidence was obtained that this phenomenon is generally applicable. The third is the in vacuo immobilization of proteins to solid supports without the use of activating chemicals. Immobilized trypsin and immobilized glycotrypsin were shown to have greatly improved thermostability and retained their full activity after repeated washings and multiple usages. The immobilized glycotrypsin has exceptional thermostability and it was demonstrated that it proteolyses native proteins at elevated temperatures without the requirement for prior denaturation. It was demonstrated that a complex protein structure, zona pellucida (ZP), could be immobilized in vacuo on a solid surface and retain its biological activity. This provides strong evidence that in vacuo immobilization is a benign chemical modification procedure which does not disrupt protein structure.
Keywords: Chemistry, Biochemistry.